Impact Of The Development Of The Internet On Students' Learning Achievement (Case Study At SMA Muhammadiyah Sawangan) - Adhillah, Annisah; Sadiyah, Nadira; Zaky, Raihan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
The author's purpose in this research is to determine the influence of the internet, the benefits and impacts of using the internet on student achievement and to find out the problems, bad effects of the internet and find solutions to the bad effects caused by the internet for students. The research approach used in this study is a qualitative approach, namely a research approach that presents data in the form of a narrative/description. The type of research we use is descriptive research. Descriptive research aims at solving problems that exist today because there are so many kinds of research that tell, analyze, and apply research with survey results, questionnaires, observations, or with text techniques, case studies, studies. time and motion, qualitative analysis, cooperative studies, or cooperative studies, or operational studies. The results of the research are the internet is very helpful in learning activities, because wherever someone can be free to find learning information.